Employment in the Shadow of Neoliberalism: A Humanitarian Overview of Global Work Environments - Mehmet Öçal; Özal Çiçek (Sosyal Siyaset Konferansları Dergisi)
The discipline of social policy was created to eradicate the adverse aspects of capitalism and make it a livable system. In contemporary terms, it is a humanity-focused political quest to eliminate social risks confronted by all social classes. The right and freedom to work are predominant elements of human life that directly affect wellbeing. They have found significance in the discipline of social policy in the conception of employment and in the struggle to make occupations more humane. The free movement of capital and neoliberal policies has transformed spatial distributions and conditions of employment worldwide, increasing inequalities among employees. Thus, diverse international organizations and trade union organizations are compelled to seek alternatives. This study evaluated the damage caused by neoliberalism to the humanitarian aspects of employment and the working conditions of the global workforce. It takes a humanitarian perspective and includes a discussion on humanitarian work conditions. The assessment incorporated the principal indicators of the labor market, including data on wages, working times, healthy and safe working conditions, social security, and union organization levels. The results revealed the existence of severe inequalities in employment conditions around the world. Further, it was apprehended that the low standards of work environments in undeveloped countries resulting from neoliberalism and globalization further intensified inequities.